A retrospective study of the prehospital burden of trauma managed by the Western Cape Government emergency medical service - Abdullah, Mohammed Naseef (Department of Surgery, 2020)
Introduction: Trauma is one of the leading causes of premature death and disability in South Africa. There is a paucity of data describing the prehospital trauma burden in sub-Saharan Africa. The aim of this study was to describe the epidemiology and common trauma emergencies managed by the Western Cape Government emergency medical service (WCG EMS) in South Africa. Methods: The WCG EMS call centre registry was retrospectively analysed for all trauma patients managed between 01 July 2017 to 30 June 2018. A descriptive analysis of the data was performed using standard procedures for all variables. To date, this was the first analysis of this dataset or any prehospital trauma burden managed in the Western Cape of South Africa. Results: The WCG EMS managed 492 303 cases during the study period. Of these cases, 168 980 (34.3%) or 25.9 per 1000 population were trauma related. However, only 91 196 met the inclusion criteria for the study. The majority of patients (66.4%) were males and between the socio-economically active ages of 21-40 years old (54.0%). Assaults were the most common cause of trauma emergencies, accounting for 50.2% of the EMS case load managed. The patient acuity was categorised as being urgent for 47.5% of the cases, and 74.9% of the prehospital trauma burden was transported to a secondary level health care facility for definitive care. Conclusion: This is the first report of the prehospital trauma burden managed in the Western Cape of South Africa. The Western Cape suffers a unique trauma burden that differs from what is described by the WHO or any other LMIC. It also provides the foundation for further research towards understanding the emergency care needs in South Africa and to support Afrocentric health care solutions to decrease this public health crisis.